2003
DOI: 10.1023/a:1021982719654
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Psychometric performance has been reported to be related to brain atrophy in cirrhotics, but the relationship between brain atrophy and EEG findings is still unknown. The aim of this study was to ascertain the relationship among brain atrophy, EEG, and cognitive performance in cirrhotics. Sixty-eight cirrhotics (age = 55 +/- 10 years; males-66%) underwent psychometric evaluation (Symbol Digit Test, Trail Making Test-Part A, Scan test), EEG recording and spectral analysis (S-EEG), and brain CT scan. Central bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(5 citation statements)
references
References 80 publications
0
5
0
Order By: Relevance
“…Patients with MHE showed more serious brain atrophy as compared with those without MHE (Guevara et al, 2011 ). A previous study has suggested that structural alterations are associated with lower psychometric performance of cirrhotic patients (Amodio et al, 2003 ).…”
Section: Introductionmentioning
confidence: 98%
“…Patients with MHE showed more serious brain atrophy as compared with those without MHE (Guevara et al, 2011 ). A previous study has suggested that structural alterations are associated with lower psychometric performance of cirrhotic patients (Amodio et al, 2003 ).…”
Section: Introductionmentioning
confidence: 98%
“…Previously published literature mostly documents abnormalities in the levels of the branched chain amino acids (Soeters and Fischer, 1976 ; Tajiri and Shimizu, 2013 ), while we observed a reduction of virtually all amino acids measured. This may relate to the notion that chronic hyperammonemia results in brain atrophy, which may be mediated by disturbed protein synthesis/regeneration due to insufficient amino acid availability (Amodio et al, 2003 ; Garcia-Martinez et al, 2011 ). Our findings may have been confounded, to some extent, by the fact that animals fed the ammonia-enriched diet most likely ate less, and tended to grow less.…”
Section: Discussionmentioning
confidence: 99%
“…Limitations to this study included that while the Scan test software provides an overall Z score, which is corrected for age/educational attainment, the presented weighed RTs were not normalised, and should be considered valid for populations of patients with cirrhosis similar to that used in this study 45 . Amodio and colleagues found that, among various types of psychometric tests such as the Trail-making Tests and Symbol Digit Modality Tests, the scan test was the most closely related to central brain atrophy 47 . About 50% of cirrhotic patients performed poorly on the scan test, making it valuable in detecting the neuropsychological impairment caused by cirrhosis.…”
Section: Diagnostic Testing For Covert Hepatic Encephalopathymentioning
confidence: 99%